A new Cladocora caespitosa population with unique ecological traits - KERSTING, D.; CEBRIAN, E.; VERDURA, J.; BALLESTEROS, E. (Mediterranean Marine Science, 2017)
The Mediterranean endemic scleractinian coral Cladocora caespitosa (L., 1767) has been recently included in the IUCN Red List as an endangered species. In this context, information on the species is urgently required to further assess its status and to determine its distribution area. This study reports on the main traits of a recently discovered C. caespitosa population in Formentera (Balearic Islands, W Mediterranean). Here, coral colonies live wrapped in Cystoseira forests thriving on rocky substrata (5 - 13 m depth), thus being a new example of the ability of C. caespitosa to build up extensive populations within algal communities. Even though coral cover reaches 20 % on average, which is a remarkable figure for this species, colonies are generally small ( 10 cm diameter on average), most probably due to partial exposure to waves and currents. The combination of hydrodynamics and the presence of algal forests in the studied site could be responsible for the high occurrence of a rare type of colony growth: free-living coral nodules or coralliths. This population is highly interesting for future monitoring owing to its unique traits, the absence of necrosis signs related to past mortality events, and its location inside a marine reserve.